Produção de polpas de mangas Tommy Atkins, na Amazônia setentrional, através da aplicação de preservativos e da pasteurização - Neves, Leandro Camargo; Benedette, Ronaldo Moreno; Da Silva, Vanuza Xavier; De Souza Prill, Marcos Andre; Vieites, Rogério Lopes [UNESP] (Soc Brasileira Fruticultura, 2007)
The present work had evaluated the efficiency of the pasteurization and the use of preservatives in mangos pulps (Mangifera indica L.) refrigerated. Before carrying out the treatments, the fruits had been cleaned in solution of sodium hypochlorite (NaOCl) at 100 mg. L(-1), for 10 minutes. After the processing, it was carried out through the adjustment of pH of pulps for 3.0 and the adjustment of the water activity (W(a)) at 0.95. The used variable had been the branching (hot water at 95 +/- 5 degrees C, for 0 and I minute), the addition of sodium benzoate in the concentrations of 0; 200 and 500 mL.L(-1) and, sulfite dioxide (SO(2)) in 0, 100 and 200 mL.L(-1). Then the pulps had been packed in low density polyethylene (LDPE) bags of 0,060 mm (0.10 x 0.12 m - without free space and content of 500g of pulp) and, conditioned in at 20 +/- 1 degrees C e 80 +/- 3% of R.H, for 28 days. At the end of the experiment, the treatments not submitted to the branching had shown the biggest ascorbic acid levels. However, in these same treatments had been noticed intense microbiological activity and raised levels of pH. There aren't significant differences between the tested treatments in the titratable acidity (TA) and soluble solids (SS) analyses. Due to the absence of black spot in the pulps used during all the experimental period, it couldn't be detected the differences between the application of the SO(2) and the use of the branching. The lower index of microbiological contamination and the preference of the judges in the sensorial panel had been attributed to the submitted treatments to the branching, addition of 500mL.L(-1) of sodium benzoate and addition of 200mL.L(-1) of sulfite dioxide.
Production of mango pulps tommy atkins in septentrional amazon through aplication of preservatives and of branching
Keywords: Mangifera indica L.; agro-industry; physics properties; sensory evaluation